Molecularly imprinted polymers coupled to mass spectrometric detection for metallothionein sensing - Vaneckova, Tereza; Vanickova, Lucie; Tvrdonova, Michaela; Pomorski, Adam; Krężel, Artur; Vaculovic, Tomas; Kanicky, Viktor; Vaculovicova, Marketa; Adam, Vojtech (Talanta, 2019)
We report a facile method for detection of metallothionein (MT), a promising clinically relevant biomarker, in spiked plasma samples. This method, for the first time, integrates molecularly imprinted polymers as purification/pretreatment step with matrix assisted laser desorption/ionization time-of-flight mass spectrometric detection and with laser ablation inductively coupled plasma mass spectrometry for analysis of MTs. The prepared MT-imprinted polydopamine layer showed high binding capacity and specific recognition properties toward the template. Optimal monomer (dopamine) concentration was found to be 16 mM of dopamine. This experimental setup allows to measure µM concentrations of MT that are present in blood as this can be used for clinical studies recognizing MT as marker of various diseases including tumour one. Presented approach not only provides fast sample throughput but also avoids the limitations of methods based on use of antibodies (e.g. high price, cross-reactivity, limited availability in some cases, etc.).
Keywords: Polymers; LA-ICP-MS; Polydopamine; metalothionein; zdraví dobrovolníci pro lékařské studie; MALDI-TOF-MS; Molecular Imprinting; Indoles; Metallothionein; Molecularly imprinted polymers; hmotnostní spektrometrie; lidé; polymery; Mass Spectrometry; Humans; molekulový imprinting; Healthy Volunteers; indoly